Mohammad Natsir, Character Education, and its Relevances to the National Education System: A Study of the Educational Thought in Effort to Build the Studentsâ Noble Characters in Indonesia - Abdullah, Anzar (TAWARIKH, 2013)
ABSTRACT: The main problem in this research is the constellation of Mohammad Natsir educational thought in an effort to build a noble character of learners in the National Education System. A primary issue is described in three sub-problems, namely: How does the concept of Islamic educational thought of Mohammad Natsir?; How does the concept of noble character that became Mohammad Natsirâs educational purposes?; and What methods of Islamic education, according to Mohammad Natsir, in an effort to build a noble character of learners? Above problems is assessed through methods of library research that is qualitative and using descriptive analysis. Data was collected through a variety of written sources, such as books, papers, magazines, and journals related to the research focus. The results showed that the concept of educational thought in Islam, according to Mohammad Natsir, to build a noble character of students, namely: (1) the Purpose of Islamic education is servitude to Allah; (2) Man/woman as an actor and educational goals, aiming to cultivate the competences of aqliyah, qalbiyah, and amaliyah; (3) Principles of Islamic education is monotheism; (4) Sources of Islamic education is the Al-Quran, Al-Sunnah, and ijtihad; and (5) Method of Islamic education is exemplary and habituation. Mohammad Natsir also stated that there are four pillars of education for Islamic ummah, namely: family, Islamic boarding schools, schools institution, and mosques. Finally, Mohammad Natsirâs thought on character education is still relevance and has become the locomotive of the birth of national education system in Indonesia.KEY WORDS: Mohammad Natsir, history of thought, concept of character education, system of national education in Indonesia, character education for students, and a good citizen.About the Author: Dr. Anzar Abdullah is a Senior Lecturer at the Department of History Education, Faculty of Education and Teacher Training UVRI (Veteran University of the Republic of Indonesia), UVRI Campus II, Jalan Baruga Raya, Antang, Makassar, South Sulawesi, Indonesia. He can be reached at: anzarabdullah91@yahoo.co.idHow to cite this article? Abdullah, Anzar. (2013). âMohammad Natsir, Character Education, and its Relevances to the National Education System: A Study of the Educational Thought in Effort to Build the Studentsâ Noble Characters in Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.5(1) October, pp.71-90. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (August 22, 2013); Revised (September 26, 2013); and Published (October 28, 2013).